Dvoglasje v Gradnikovi poeziji - Mitrović, Marija (Slavistična revija, 1999)
Gradnik lent his voice and he duplicated it, i.e., another person's voice can heard besides the voice of the lyrical subject. The polyphony brought him envialbe reputation among the Slovene lyric poets. Where this polyphony is missing, the "real", aesthetically relevant Gradnik is considerably reduced. the author attemps to develop this hypothesis into a thesis, extending her research particularly into the area of the literary expression itself, which could be called "the syntax of poetry".
Keywords: Gradnik, Alojz; literarne študije; slovenska književnost; slovenska poezija